The vulnerable blood - Hess, K. (Hämostaseologie, 2015)
Patients with diabetes are at increased risk of cardiovascular morbidity and mortality. While arteriosclerotic lesions have long been recognized as the underlying cause more recent studies suggest that alterations of the blood are also critically involved. Following plaque rupture, adherence of platelets is followed by the formation of a cross-linked fibrin clot. Patients with diabetes exhibit a prothrombotic milieu consisting of hyper reactive platelets, a tight and rigid clot structure which is due to up-regulation of coagulation factors and prolongation of clot lysis. Metabolic alterations as well as inflammatory processes, which are up–regulated in diabetes, are thought to be the main underlying causes. More recently, the complement cascade has emerged as a potential new player in this context with several complement components directly influencing both platelet function and coagulation.This review provides an overview concerning the changes that lead to alterations of platelet function and clot structure in diabetes.
Keywords: Diabetes mellitus; coagulation; clot; complement